Passport fee – its legal nature, structure, functions and purpose of proceeds - Zbigniew Ofiarski (Prawo Budżetowe Państwa i Samorządu)
This article presents the elements of the legal structure of a passport fee. Author identifies its legal nature, performed functions and analyses rules of collection of this fee which are regulated in the provisions of the Passport Documents Act. Payment of the passport fee is a necessary condition for initiating a procedure of issuing or refusing to issue a passport. The obligation to pay that fee is related to the issuance of a passport and temporary passport and does not cover the procedure of issuing diplomatic and service passports. Passport fees are a source of a state budget revenue collected by voivodes and consuls. The Passport Documents Act establishes the subject of the passport fee, the entities obliged to pay it, exemptions from this obligation and the rules to be established by the Council of Ministers on determining the rates of these fees, including reduced rates. For the purpose of a comparison, selected legal acts regulating the scope of an application of passport fees in Poland in the interwar period and in the years preceding the political and economic transformation initiated in 1990 were analysed. The study positively verified the thesis on the public-law nature of the passport fee. It was established that it performs fiscal and non-fiscal functions. In the course of the research, the dogmatic and legal method was applied and, complementarily, empirical and analytical method.